Catalytic signal of rabbit liver metallothionein on a mercury electrode: a combination of derivative chronopotentiometry with adsorptive transfer stripping - Trnková, Libuse; Kizek, René; Vacek, Jan (Bioelectrochemistry (Amsterdam, Netherlands), 2002)
Constant current chronopotentiometric stripping analysis (CPSA) in combination with adsorptive transfer stripping (AdTS) technique was used to study the rabbit liver metallothionein (MT) on a hanging mercury drop electrode (HMDE). Metallothionein yielded a distinct, sharp chronopotentiometric signal at very negative potentials (about -1.7 V), also known as the "peak H". The height and potential of this peak were dependent on experimental conditions, such as buffer composition, pH, and the presence oxygen in solutions. The peak H was highest in borate buffer with pH close to the isoelectric point (pI) of MT. The chronopotentiometric results contribute to a deeper understanding of the nature of catalytic hydrogen evolution and demonstrate the usefulness of the peak H in peptide and protein research.
Keywords: králíci; Rabbits; metalothionein; Catalysis; elektrody; rtuť; Potentiometry; Metallothionein; potenciometrie; Adsorption; Animals; Electrodes; Liver; Mercury; játra; katalýza; zvířata; adsorpce